Dissecting the roles of VP0 cleavage and RNA packaging in picornavirus capsid stabilization: the structure of empty capsids of foot-and-mouth disease virus - Curry, Stephen; Fry, Elizabeth; Blakemore, Wendy; Abu Ghazaleh, Robin; Jackson, Terry; King, Andrew; Lea, Susan; Newman, John; Stuart, David (American Society for Microbiology, 1997)
Empty capsids of foot-and-mouth disease virus (FMDV) type A22 Iraq 24/64, whose structure has been solved by X-ray crystallography, are unusual for picornaviruses since they contain VP2 and VP4, the cleavage products of the protein precursor VP0. Both the N terminus of VP1 and the C terminus of VP4, which pack together close to the icosahedral threefold symmetry axis where three pentamers associate, are more disordered in the empty capsid than they are in the RNA-containing virus. The ordering of these termini in the presence of RNA strengthens interactions within a single protomer and between protomers belonging to different pentamers. The disorder in the FMDV empty capsid forms a subset of that seen in the poliovirus empty capsid, which has VP0 intact. Thus, VP0 cleavage confers stability on the picornavirus capsid over and above that attributable to RNA encapsidation. In both FMDV and poliovirus empty capsids, the internal disordering uncovers a conserved histidine which has been proposed to be involved in the cleavage of VP0. A comparison of the putative active sites in FMDV and poliovirus suggests a structural explanation for the sequence speciﬁcity of the cleavage reaction